Search for Principle - The Government’s Liability in Negligence for the Careless Exercise of its Statutory Powers - Geuther, Thomas (Victoria University of Wellington Law Review, 2000)
For many years the English courts have struggled to develop a principled approach for determining when a public authority can owe a duty of care in respect of the exercise of its statutory powers. Initially, public authorities received no special treatment. Then the courts conferred an almost complete immunity on them, requiring public law irrationality to be established before considering whether a duty could arise. The English approach has not been adopted elsewhere in the Commonwealth. The High Court of Australia and the Supreme Court of Canada have developed different tests, and the New Zealand courts, while never explicitly rejecting the English position, have never followed it. This paper argues that a modified version of the Canadian Supreme Court’s approach should be adopted in New Zealand. It proposes that irrationality be a precondition to the existence of a duty of care only where policy considerations are proved to have influenced the decisions of a public authority in exercising its statutory powers.